KUNAERNE KÆMPER - MED MYTE OG METAFOR - Tuxen, Vibeke (Tidsskriftet Antropologi, 1996)
Vibeke Tuxen: The Kunas Struggle - with Myth and Metaphor The author is working with the kuna people on a demarcation project and observes how the kuna use their myths and metaphors in practice to analyse the presence of foreigners, whom experience has taught them not to trust, but on whom they also depend for their territory. The myth of Duiren who taught the Kunas to resist and fight for their culture but who also depended on the help of other people, is put forward by a chief in his chanting, analysing the present situation. Kuna myths form a total of interrelated stories, which on the one hand form the mind of the Kuna chief in his analysis, and on the other hand certain parts, or myths, are being picked out to show the angle that the chief wishes to put forward to his people. Personal names can be changed and molas can be sold. Myths, names, and molas are three ways in which the Kuna relate themselves to the outer world and still maintain their own way of living. Through all three, foreign aspects can be expressed, let in, and let out again.